OPTIMALISASI DESAIN JIG VALVE SPRING COMPRESSOR DENGAN DOUBLE FLANGE UNTUK EFISIENSI PELEPASAN DAN PEMASANGAN KATUP MESIN - Dewi, Renita; Fatin, Shafa Amatullah; Wijaya, Krisna Chandra; Ramadhani, Anisa; Heryana, Ghany (P3M Politeknik Negeri Indramayu, 2025)
This research aims to develop a new design of Jig Valve Spring Compressor that uses double flange, replacing the previous design that only uses one flange. This new design, which is still under development, has the potential to increase the speed and efficiency of the cylinder head overhaul process which has previously shown an increase in time efficiency of up to 82%. The development of this design is based on ergonomic principles using the OWAS method to minimize the risk of musculoskeletal injuries and improve the working comfort of technicians during the engine valve removal and installation process.